PENGELOLAAN PENILAIAN HASIL BELAJAR MATA PELAJARAN BAHASA INGGRIS MTs PADA ASPEK PENGETAHUAN - Siti Nurhayati (Balai Diklat Keagamaan Bandung, 2019)
The purpose of writing this article to describe how to process the results of the assessment of the aspects of knowledge made by MTs English teachers, both in assessing the learning process and student learning outcomes. Assessments made by teachers in determining the student's final grade, consisting of the Daily Test Score , the Mid-Term Test Score and the End-Year Test Score . This assessment is carried out to measure students' abilities in the form of factual, conceptual, procedural, and metacognitive knowledge, as well as low to high level thinking skills. The competency measured in this activity is related to the achievement of Basic Competence (KD) on KI-3 conducted by MTs English subject teachers. The assessment technique used is in accordance with the characteristics of each. These include written tests, oral tests, and assignments. The method used in writing this article is descriptive analytic, to describe the ability of English MTs teachers, in making decisions using information obtained through measurement of student learning outcomes. As for the results of this writing, teachers are expected to be able to process the results of the assessment of knowledge used for the benefit of learning. For this reason, teachers must be able to process the results of the assessment of knowledge for various purposes, including to determine the success of learning, to do remedial or for enrichment. Key words: Evaluation; Knowledge; test.